Pengembangan Model Pembelajaran Bahasa Inggris berbasis kompetensi di Program Studi Bahasa Inggris Pada PTAIN di Wilayah DKI Jakarta, Banten dan Jawa Barat - M. Fakhan, Frans Sayogie dan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
This research aims at knowing the theories of English learing process based on communicative approach andÂ developing a model for English learning pertaining to competent-based cumiculum. This model will be needed for EnglishÂ teachers to eliminate problems when they implement the curriculumÂ